Adult Sellar Region Atypical Teratoid/Rhabdoid Tumor: A Retrospective Study and Literature Review - Liu, Fujun; Fan, Shucai; Tang, Xin; Fan, Shuangmin; Zhou, Liangxue (Frontiers in Neurology, 2020)
Background Adult sellar region atypical teratoid /rhabdoid tumor (AT/RT) is a rare lesion. We aimed to elucidate clinical, radiologic, and pathological characteristics, treatment strategies, and outcomes of this disease. Methods Five adult sellar AT/RT patients were retrospectively analyzed between January 2015 and December 2018. Additionally, we performed a review of the reported data on adult sellar AT/RT. Results Patients (n = 5) were female with a median age of 50 years. The mean duration of symptoms, of which headache was the most frequent, was 1.6 months (range, 2 weeks to 8 months). The average tumor size was 2.82 cm (range, 1.9 to 4.5 cm). All lesions were irregularly shaped. Magnetic resonance imaging showed heterogeneous enhancement in three of five lesions. Four of five patients underwent subtotal resection (STR) and one gross total resection (GTR). Whereas one patient received postoperative adjuvant radiotherapy, one patient received postoperative combination of radio- and chemotherapy. The review of the reported data showed that 39 cases of adult sellar AT/RT had been reported. The estimated median overall survival (OS) was 23 months with a 1-year survival estimate of 59.7%. The median OS for patients with GTR was 28 months and 17 months for patients with STR. Kaplan-Meier analysis showed that patients with high (≥35%) MIB-1/Ki67 index value had a significantly shorter OS compared to those with low (<35%)index value (p=0.033), and that patients who received postoperative combination radio-and chemotherapy had longer OS than that of those who didn’t (p<0.001). Conclusion Adult sellar region AT/RT is a rapidly growing tumor with a poor prognosis. High levels of MIB1/Ki-67 on histology may indicate aggressive feature of the tumor. Maximal safe resection followed by adjuvant radiotherapy combined with chemotherapy may be the optimal therapeutic strategy for adult sellar region AT/RT.